In-Vitro Technique For Resistance Evaluation of Rice Varieties Against Blast Disease (Pyricularia oryzae Cav.) - Tarkus Suganda; Puspa Radityo Putri; Gabbi Andria Dwitia Putri (CROPSAVER, 2019)
Blast, incited by Pyricularia oryzae Cav. is the most yield-limiting disease of rice.  Use of resistant varieties is the most suggested tactic for controlling this disease. Therefore, resistant varieties are continuosly developed in rice breeding program. One of the challenges in developing resistant varieties to blast is the testing methods which required the availability of optimum condition for infection and development of disease, especially it has to be done against different races of the fungus. In addition, the duration of test is required long period of time. In order to shorten the test, the in-vitro technique has been studied using inoculation to rice leaf cuts incubated in a petridishes amended with several layer of wetted sterilzed tissue.  Tests used four differenet domonant races of the fungus, i.e. 033, 073, 133, and 173, wehereas the rice cultivars used were Kencana Bali (susceptible to all races), Situ Patenggang (resistant and moderately resistant), Arize (moderately resistant to race 073) and PP3, a breeding line. Plants were scored using a pictorial scorring scale of IRRI (1996). The results showed that the in-vitro technique using leaf cuts was able to separate the reaction of the resistant from of the susceptible rice to blast disease. It confirmed the reaction of the result of standard greenhouse test. Cultivar Kencana Bali was consistantly susceptible to ras 173 both in in-vitro, standard greenhouse, and in field. The in-vitro technique was able to speed up the inoculation process, prevent a mix of races and release of races to environment. It also can minimize cost of testing, and speed up the selection process of resistance in plant breeding to develop blast resistant varieties.